Organizational Culture and Safety: Taking the Hungarian Electricity Industry as An Example - Vasvári, Fanni; Juhász, Márta; Krasz, Katalin Gerákné (Journal of risk analysis and crisis response, 2024)
Introduction: This study focuses on one of the largest Hungarian companies with a century-long history in the electricity supply business. It aims at examining the relationship between leadership style and safety-awareness in the perceptions of leaders and subordinates. Method: Middle-level managers (N=163) completed the MLQ. Subordinates (N=650) completed the MLQ and expanded with specific subscales, along which employees judged the leadership style of their managers. We relied on some approaches and on analysis of the interviews with participants. To measure safety-awareness, we use 3 different scales. Results: Based on the results, in the subordinates’ sample, all scales of Transformational leadership positively significantly correlated with all component of safety-awareness, while all scales of Transactional leadership negatively significantly correlated with every component of safety-awareness. In the managers’ sample, both the Transformational and Transactional leadership showed a significant positive correlation with all component of safety-awareness except for the Laissez-Faire leadership, where a negative significant relationship was found. Conclusions: In case of subordinates, safety-awareness is associated with their leader’s transformational leadership. From the perspective of managers, it appears that a basic level of safety-awareness is associated to Transactional leadership traits, while a higher level of safety-awareness requires a Transformational leadership.